Understanding an Introverted Child: A Narrative Study - Ahmet Saban; Serap Sarıçelik (Anı Publishing, 2018)
This study examined Teacher Serap's (the second author of this study) effort to recognize and reach an introverted student in her classroom based on her own experiences. The study was conducted within the scope of the "narrative research" methodology, one of the qualitative research designs. The main purpose of narrative studies is to examine the ways through which individuals experience the world and reality by analyzing their own personal stories. From this point of view, this study examined Teacher Serap's experiences with an introverted student in her classroom through her own personal stories and the changes that these experiences caused both in the introverted student and her profession. Data were collected through a series of semi-structured interviews. After each interview was transcribed, written feedback from the teacher was obtained through e-mails and new interviews were conducted with her about the issues that were not clear enough. In addition, after finishing the writing of the research report, Teacher Serap was invited to indicate her opinions on the entire report. Data were reorganized around the sub-questions of the study and presented in a chronological framework under five themes. They include: (1) recognizing the introverted student, (2) getting to know the introverted student, (3) reaching the introverted student, (4) tracing the changes in the introverted student, and (5) evaluating the professional attainments. According to the findings, Teacher Serap believes that she has achieved her desired goals for her introverted student and developed an invaluable understanding about the phenomenon of difficult children. The study concludes that there is a need for comprehensive narrative research studies to be carried out on other types of difficult children.